Interpreting Personalized Industrial Heritage in the Mining Towns of Cumberland County, Nova Scotia: Landscape Examples from Springhill and River Hebert - Summerby-Murray, Robert (Urban History Review / Revue d'histoire urbaine, 2007)
As analysis of deindustrialization shifts from economic processes to community response, public landscapes become the locus for the struggle over memory. The interpretation of collective memory has been considered through oral histories, worker narratives, and public art. Missing from this analysis, however, are the personalized landscapes that also contribute to the understanding of industrial heritage in deindustrializing cities and small towns. This article considers a small number of artifacts and constructed objects that create personalized landscapes of industrial heritage in two mining towns in Cumberland County, Nova Scotia. Interpreting these landscapes highlights their ambiguity, the contributions they may make to processes of local cultural resistance, and their intensely personal motivation. The analysis questions the extent to which these landscapes reflect a wider coherent heritage discourse or function to reinforce local community, family, and place identity.